Reusing of Organic Waste from Tubifex sp. Substrate in nature - Shafruddin, D.; Efiyanti, W.; Widanarni, . (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This study was conducted to determine whether organic waste from the substrate of Tubifex sp. can be used as inoculants to produce them through culture. Substrate used was the mix of mud and chicken manure by ratio of 1:1, placed on the container 80×20×15 cm, water elevation 2 cm, and water debit 300 ml/min. Inoculants number was ranged from 57 to 60 Tubifex sp. per container. The length of Tubifex sp. body was ranged from 0.9 to 3.5 cm and an individual mean weight of 2.78 mg. Organic waste applied was 500 g, 1000 g, and 1500 g. Rearing was performed for 50 days. During experiment chicken manure of 0.075 g/m2 was added into culture every day. The results of study showed that higher population of Tubifex sp. (174,227 tails/m2; 413.7 gram wet weight) was obtained by using 1000 g of organic waste. Thus, organic waste derived from the substrate of Tubifex sp. from the nature can be reused to culture Tubifex sp. at the controlled container. Keywords: Tubifex, organic waste, population ABSTRAK Penelitian ini dilakukan untuk mengetahui apakah limbah organik sisa hasil penangkapan cacing sutera dari alam dapat digunakan sebagai inokulan untuk memproduksi cacing sutera melalui kegiatan budidaya. Substrat yang digunakan berupa campuran lumpur dan kotoran ayam dengan perbandingan komposisi masing-masing 1:1, ditempatkan dalam wadah berukuran 80×20×15 cm, debit air 300 ml/menit/wadah, dan tinggi air 2 cm. Jumlah cacing yang ditebar antara 57 - 60 ekor, panjang cacing 0,9 - 3,5 cm, dengan bobot individu rata-rata 2,78 mg. Limbah organik sebagai inokulan awal cacing sutera masing-masing seberat 500 g, 1.000 g dan 1.500 g. Pemeliharaan dilakukan selama 50 hari. Selama pemeliharaan dilakukan pemupukan menggunakan kotoran ayam sebanyak 0,075 g/m2 setiap hari. Hasil penelitian menunjukkan bahwa populasi cacing tertinggi diperoleh dengan menggunakan limbah organik sebanyak 1.000 gram (174.227 ekor/m2; 413,7 g). Dengan demikian, limbah organik substrat cacing sutera dari alam dapat digunakan kembali untuk budidaya cacing di wadah terkontrol. Kata kunci: Tubifex, limbah organik, populasi